Can there be a Biography of a Book?: Comparative Observations on Publications by Francysk Skaryna and Erik Pontoppidan - Raven, James (Knygotyra, 2023)
In a comparison of bibliographical approaches to Francysk Skaryna’s The Little Traveller’s Book (1522) and Erik Pontoppidan’s Natural History of Norway (1752) this article argues that attempts to write a book biography can benefit from extensive archival research as well as close physical examination of surviving copies, using new forensic technologies as well as adapting more traditional modes of investigation. Ultimately, however, the concept of ‘biography’ or ‘life cycle’ is questioned. The article examines the intellectual genesis, writing, translation, critical review, reception and collection of the Natural History as well as its extraordinary legacy – a legacy that is helpfully comparable to and distinctive from that of Skaryna’s work. Both writers moved in a world of circuits, of typographical and bibliographical innovation and comment, of travel and translation, of new and emergent accessibility to language and books – all, from their perspective, from the beneficence of God and to His glorification. Skaryna’s journey took him from Polatsk and Vilnius to Kraków and Padua, to his first Psalter and other biblical publishing in Prague and his The Little Traveller’s Book in Vilnius, to travels to Moscow, Poznan, Königsberg and back to Vilnius and Prague. As with Skaryna, Pontoppidan engaged in wide travel, also establishing far flung contacts and correspondence. Both faced constraints, and most notably the impact of war, disease, political and religious intervention and fires that destroyed cities and printing houses. Both writers were determined to write in the vernacular, Skaryna working to translate and create new type, all to make books of the Bible available in an accessible language. Skaryna contributed to the development of the Belarusian literary language just as Pontoppidan’s writing and interest in dialect contributed both to the standardization of Danish and the distinctive linguistic origins of Norwegian. Both composed prefaces to their editions, in which they emphasized that the purpose of their publishing activities was to help ordinary people, in Skaryna’s words to “become acquainted with wisdom and science.” The legacies of both diverged from literary references and directly derivative sightings of sea monsters in the case of Pontoppidan, to numerous statues and other material commemorations in the case of Skaryna who remains embroiled symbolically in different claims over national identities. The concluding assessment of whether such study can contribute to a ‘book biography’ or ‘life cycle’ is guarded, suggesting alternative concepts that might be tested. This includes the idea of a ‘book biology’ whereby, in such study of a ‘life’, a book is conceived by its intellectual creator with very specific intentions and is then transmuted by other actors and agencies into different material, visual and linguistic forms. In the case of Skaryna, the creations amounted to numerous unstable texts, variously arranged, with uncertain survival rates and relatively poor evidence of use. In the case of Pontoppidan, three more stable editions, Danish, German and English, were all also materially different and each copy reproduced in separate operations of printing and collation. Each copy pursued thereafter its own life – no more reproduction and so no book genealogy – but hugely diverse and differently influential lives. In such ways the biosphere might be renamed the bibliosphere. Some book lives were terminated in relative infancy, some moved around the world and through many hands, some mutilated, others preserved in situ and symbolically represented at anniversaries or for political and cultural ends.